Applications of water molecules for analysis of macromolecule properties - Mitusińska, Karolina (Comput Struct Biotechnol J, 2020)
Water molecules maintain proteins’ structures, functions, stabilities and dynamics. They can occupy certain positions or pass quickly via a protein’s interior. Regardless of their behaviour, water molecules can be used for the analysis of proteins’ structural features and biochemical properties. Here, we present a list of several software programs that use the information provided by water molecules to: i) analyse protein structures and provide the optimal positions of water molecules for protein hydration, ii) identify high-occupancy water sites in order to analyse ligand binding modes, and iii) detect and describe tunnels and cavities. The analysis of water molecules’ distribution and trajectories sheds a light on proteins’ interactions with small molecules, on the dynamics of tunnels and cavities, on protein composition and also on the functionality, transportation network and location of functionally relevant residues. Finally, the correct placement of water molecules in protein crystal structures can significantly improve the reliability of molecular dynamics simulations.